2019
DOI: 10.1101/712844
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Point-of-Use Detection of Environmental Fluoride via a Cell-Free Riboswitch-Based Biosensor

Abstract: Advances in biosensor engineering have enabled the design of programmable molecular systems to detect a range of pathogens, nucleic acids, and chemicals. Here, we engineer and field-test a biosensor for fluoride, a major groundwater contaminant of global concern. The sensor consists of a cell-free system containing a DNA template that encodes a fluoride-responsive riboswitch regulating genes that produce a fluorescent or colorimetric output. Individual reactions can be lyophilized for long-term storage and det… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(62 citation statements)
references
References 33 publications
5
57
0
Order By: Relevance
“…While CFPS conditions may vary according to the unique transcription/translation requirements for the synthesis of individual proteins, these reactions can be tailored by optimizing concentrations of the CFPS reagents. As such, CFPS has enabled a wide range of applications in directed evolution, synthetic biology, glycoscience, metabolic engineering, and education (Des Soye, Gerbasi, Thomas, Kelleher, & Jewett, 2019; Harris & Jewett, 2012; Karim & Jewett, 2016; Karim et al, 2020; Kightlinger et al, 2019; Lin et al, 2020; Martin et al, 2018; Silverman et al, 2020; Stark et al, 2019; Thavarajah et al, 2020). LETs offer a unique advantage over their circular counterparts because extensive plasmid construction steps are not required.…”
Section: Introductionmentioning
confidence: 99%
“…While CFPS conditions may vary according to the unique transcription/translation requirements for the synthesis of individual proteins, these reactions can be tailored by optimizing concentrations of the CFPS reagents. As such, CFPS has enabled a wide range of applications in directed evolution, synthetic biology, glycoscience, metabolic engineering, and education (Des Soye, Gerbasi, Thomas, Kelleher, & Jewett, 2019; Harris & Jewett, 2012; Karim & Jewett, 2016; Karim et al, 2020; Kightlinger et al, 2019; Lin et al, 2020; Martin et al, 2018; Silverman et al, 2020; Stark et al, 2019; Thavarajah et al, 2020). LETs offer a unique advantage over their circular counterparts because extensive plasmid construction steps are not required.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have demonstrated proof-of-concept field deployment of other kinds of cell-free sensing platforms, a portable colorimetric detection platform for sensing of endocrinedisrupting chemicals using cell-free protein synthesis of an allosterically activated fusion protein 110 , as well as a riboswitchbased sensor for colorimetric detection of fluoride contamination in groundwater samples which was capable of detecting concentrations around 2 ppm (the EPA limit) 111 . Jung et al 112 demonstrated detection of a wide range of common water contaminants in municipal water samples including small molecules, metals, and antibiotics using RNA Output Sensors Activated by Ligand Induction (ROSALIND), a sensing platform employing allosteric regulation of in vitro transcription of fluorescence-activated RNA aptamers.…”
Section: Biosensingmentioning
confidence: 99%
“…All three of these platforms were demonstrated to be lyophilizable and shelf stable for at least 2.5 months. In addition, they all require 37°C incubation which has been demonstrated to be achievable using a low-cost handwarmer as well as by using a patient's own body temperature 111 . Overall, the field-ready features demonstrated by these platforms are quite promising in terms of enabling their deployment in settings with limited or no power.…”
Section: Biosensingmentioning
confidence: 99%
“…Cell-free biosensing is emerging as a low-cost, easy-to-use and field-deployable diagnostic technology that can be applied to detect a range of contaminants related to human and environmental health [1][2][3]. At their core, these systems consist of two layers: a sensing layer that includes an RNA or protein-based biosensor and an output layer that includes a reporter construct.…”
Section: Introductionmentioning
confidence: 99%